The impact of COVID‐19 lockdown on glycaemic control and use of health services among children followed at a Danish diabetes clinic. (5th October 2021) - Kofoed, Poul‐Erik; Timm, Signe
Abstract: Aim: During COVID‐19 restrictions, the paediatric clinic only accepted essential outpatient visits, schools closed, sports activities and social life were limited. Most employees worked at home. This quasi‐experiment evaluates how this affected glycaemic control and use of health services among children with diabetes. Methods: Paired t ‐tests were used to compare HbA1c‐values before, during and after lockdown. Sub‐analyses were stratified by pre‐lockdown HbA1c‐values. Results: Overall mean HbA1c decreased from 58.3 to 56.9 mmol/mol ( p = 0.025) from pre‐ to post‐lockdown, a decrease also seen during the same season the previous year. HbA1c decreased by −4.2 mmol/mol ( p = 0.002) for patients with pre‐lockdown HbA1c > 59 mmol/mol, but increased slightly by 0.8 mmol/mol ( p = 0.176) for patients with HbA1c < 52 mmol/mol. HbA1c measured 8 months post‐lockdown increased again, most pronounced for patients with lowest HbA1c. During lockdown, virtual contacts increased from 0.1 to 0.5 contacts/patient/month and stayed post‐lockdown at 0.3 contacts/patient/month. Conclusion: Compared to 2019, overall the COVID‐19 restrictions did not influence the glycaemic control negatively. However, patients with pre‐lockdown HbA1c < 52 mmol/mol experienced a deterioration, whereas those with HbA1c > 59 mmol/mol experienced an improvement. Less stress and more contact with parents may contribute to the last‐mentioned finding. The lockdown enforced more virtual contacts between patients and the clinic.